Application of virtual reality for risk assessment and training in the minerals industry - Williams, Matthew James (2000)
The minerals industry often requires people to work in hazardous environments, these environments are constantly increasing in size and complexity as organisations look for new more cost-effective ways of extracting resources. Not only does this size and complexity bring with it additional safety concerns, the introduction of new legislation has placed the responsibility of employee safety with the organisation. Safety has become an important consideration, where once it might have been viewed as costly and counterproductive, organisations are now seeking to gain competitive advantage in this area. Two key areas of a successful safety management programme are risk assessment and training. These are important in designing systems and environments that are as safe as possible and in educating and training personnel to operate safely within those environments.